Complexes of Palladium (II) and Platinum (II) with Some Bidentate Ligands - Hazarika, T.N. (Asian Journal of Chemistry, 2010)
PdCl2 and K2PtCl4 react with some heterocyclic N-donor bases producing compounds of the type MLCl2 where M ═ Pd(II) or Pt(II) and L ═ 1, 10 phenanthroline (o-phen), 2,2-bipyridyl (bipy) and 2,2-biquinoline (biqn). These compounds were characterised by elemental analyses, IR and UV-visible spectra. All the complexes have square planar geometry.